The road to the teaching profession and the motives of choice, in light of autobiographical statements of students of pedagogical studies - Wanda Dróżka; Joanna Maria Madalińska-Michalak (University of Lower Silesia, 2017)
This paper presents the results of qualitative research on the path to teaching as a career and the accompanying motivation. In the research, biographical, socio-cultural and economic conditions are critically considered. The study was conducted during the 2013-14 academic year in the University of Jan Kochanowski's the Department of Education and the Arts. It involved 65 prospective teachers-postgraduate students in teacher education, with a specialization in preschool and early education with English language teaching. The research used the authobiographical method on the theme "My Way to the Teaching Profession: Autobiographical and Socio-cultural Context." The study allowed the researchers to gain knowledge about the formation of the path to the teaching as a career and the prospective teachers' motivations. The paper presents the broader context of prospective teachers' formation and development. The results of the research enrich knowledge of teaching as a career and the professional development of teachers under modern conditions.